2020
DOI: 10.1093/infdis/jiaa619
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dengue Transmissions in Singapore Attributable to SARS-CoV-2 Social Distancing Measures

Abstract: Social distancing (SD) measures aimed at curbing the spread of SARS-CoV-2 remain an important public health intervention. Little is known about the collateral impact of reduced mobility on the risk of other communicable diseases. We used differences in dengue case counts pre- and post implementation of SD measures and exploited heterogeneity in SD treatment effects among different age groups in Singapore to identify the spillover effects of SD measures. SD policy caused an increase of over 37.2% in dengue case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 12 publications
0
39
2
Order By: Relevance
“…Nonetheless, the group-level shift towards peridomestic activities and increased tick exposure indicates either an increase in the overall tick population or increased exposure in those settings where participants are less inclined to use preventative measures against tick bites 30 . A similar pattern was observed for mosquito-borne disease in two studies on dengue infection: i) a simulation model found that COVID-19 stay-at-home measures (in which 70% of the population restricted their mobility to their house) led to an increase in overall infections and increased clustering of cases at the household level 42 ; and b) an empirical study using dengue case report data in Singapur found a 37.2% increase in the number of cases from expected baseline levels attributed to COVID-19 stay-at-home measures 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the group-level shift towards peridomestic activities and increased tick exposure indicates either an increase in the overall tick population or increased exposure in those settings where participants are less inclined to use preventative measures against tick bites 30 . A similar pattern was observed for mosquito-borne disease in two studies on dengue infection: i) a simulation model found that COVID-19 stay-at-home measures (in which 70% of the population restricted their mobility to their house) led to an increase in overall infections and increased clustering of cases at the household level 42 ; and b) an empirical study using dengue case report data in Singapur found a 37.2% increase in the number of cases from expected baseline levels attributed to COVID-19 stay-at-home measures 43 .…”
Section: Discussionmentioning
confidence: 99%
“…SARSeq might also be suitable to test symptomatic persons if a turnaround of 24h for the test itself is acceptable. In addition, SARSeq can be implemented in epidemiology studies to understand the spreading dynamics of infections 45 and to investigate interaction between different pathogens across large populations 46 . However, the main advantage of SARSeq is that the same turnaround time of 15-24 hours can be used to simultaneously test tens of thousands of samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many of these dormitories are sited well away from the residential areas that house the general population, offering increased protection from public and private residential developments that were historically more prone to dengue outbreaks. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Within the general community, dengue transmission risk increased during the period of intensified social distancing measures, suggesting that home residences remained as key transmission sites. 9 Domestic and relatively localized outdoor transmission was identified as a primary pathway in Thailand where 60% of dengue cases living <200 m apart were identified as being from the same transmission chain as opposed to 3% which were separated 1 to 5 km apart. 26 In Brazil, 70.4% (95% CI: 58.2% to 79.8%) of individual transmission events occurred within 500 m, 27 and in Vietnam, households were described as foci for dengue transmission in highly urbanized areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation